Discretization of convective fluxes in Navier-Stokes equations on the basis of high-resolution difference schemes - Volkov, K.N. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2004)
The properties of high-resolution finite difference schemes designed for the discretization of convective fluxes in Navier-Stokes equations and the features of their numerical implementation are considered. The finite difference schemes are developed on nonuniform grids; normalized variable diagrams are used to analyze their properties. Some simulation results for flow of viscous incompressible fluids in a lid-driven cavity obtained with the aid of different schemes are compared.